Systemic and local granzyme B levels are associated with disease activity, kidney damage and interferon signature in systemic lupus erythematosus. (5th September 2017) - Kok, Helena M.; van den Hoogen, Lucas L.; van Roon, Joel A. G.; Adriaansen, Elisabeth J. M.; Fritsch-Stork, Ruth D. E.; Nguyen, Tri Q.; Goldschmeding, Roel; Radstake, Timothy R. D. J.; Bovenschen, Niels
Abstract: Objectives: Granzymes (Grs) are serine proteases that eliminate virally infected or tumour cells by inducing apoptosis. GrB has been shown to be associated to the pathophysiology of SLE, whereas the role of the other Grs in SLE remain unknown. Methods: Gr levels were determined in the serum of SLE patients and controls and linked to SLE activity parameters, including the IFN signature. In addition, GrB expression was investigated in LN biopsies and correlated to kidney function parameters and disease severity. Results: Serum GrK and GrM levels were not elevated in SLE and did not correlate with disease activity. In contrast, GrB was increased in SLE serum, which correlated to both the SLEDAI and IFN signature. GrB expression was detected in LN tissue biopsies. The number of GrB-positive cells in tissue correlated to several kidney function parameters (e.g. serum creatinine, proteinuria) and to the LN chronicity index. Conclusion: GrB, but not GrK and GrM, is increased in the serum and kidney of patients with SLE and correlates with measures of poor prognosis in LN. These data suggest that GrB may contribute to the pathogenesis of SLE/LN, which indicates the possibility that GrB might be used as a biomarker and/or a therapeutic target.